2.1.19 Problem 19
Internal
problem
ID
[9090]
Book
:
Second
order
enumerated
odes
Section
:
section
1
Problem
number
:
19
Date
solved
:
Monday, January 27, 2025 at 05:37:15 PM
CAS
classification
:
[[_2nd_order, _missing_y]]
Solve
\begin{align*} {y^{\prime \prime }}^{2}+y^{\prime }&=x \end{align*}
Solved as second order missing y ode
Time used: 0.581 (sec)
This is second order ode with missing dependent variable \(y\). Let
\begin{align*} u(x) &= y^{\prime } \end{align*}
Then
\begin{align*} u'(x) &= y^{\prime \prime } \end{align*}
Hence the ode becomes
\begin{align*} {u^{\prime }\left (x \right )}^{2}+u \left (x \right )-x = 0 \end{align*}
Which is now solved for \(u(x)\) as first order ode.
Let \(p=u^{\prime }\left (x \right )\) the ode becomes
\begin{align*} p^{2}+u -x = 0 \end{align*}
Solving for \(u \left (x \right )\) from the above results in
\begin{align*}
\tag{1} u \left (x \right ) &= -p^{2}+x \\
\end{align*}
This has the form
\begin{align*} u=xf(p)+g(p)\tag {*} \end{align*}
Where \(f,g\) are functions of \(p=u'(x)\). The above ode is dAlembert ode which is now solved.
Taking derivative of (*) w.r.t. \(x\) gives
\begin{align*} p &= f+(x f'+g') \frac {dp}{dx}\\ p-f &= (x f'+g') \frac {dp}{dx}\tag {2} \end{align*}
Comparing the form \(u \left (x \right )=x f + g\) to (1A) shows that
\begin{align*} f &= 1\\ g &= -p^{2} \end{align*}
Hence (2) becomes
\begin{equation}
\tag{2A} p -1 = -2 p p^{\prime }\left (x \right )
\end{equation}
The singular solution is found by setting \(\frac {dp}{dx}=0\) in the above which gives
\begin{align*} p -1 = 0 \end{align*}
Solving the above for \(p\) results in
\begin{align*} p_{1} &=1 \end{align*}
Substituting these in (1A) and keeping singular solution that verifies the ode gives
\begin{align*} u \left (x \right ) = x -1 \end{align*}
The general solution is found when \( \frac { \mathop {\mathrm {d}p}}{\mathop {\mathrm {d}x}}\neq 0\). From eq. (2A). This results in
\begin{equation}
\tag{3} p^{\prime }\left (x \right ) = -\frac {p \left (x \right )-1}{2 p \left (x \right )}
\end{equation}
This ODE is now solved
for \(p \left (x \right )\). No inversion is needed.
Integrating gives
\begin{align*} \int -\frac {2 p}{p -1}d p &= dx\\ -2 p -2 \ln \left (p -1\right )&= x +c_1 \end{align*}
Singular solutions are found by solving
\begin{align*} -\frac {p -1}{2 p}&= 0 \end{align*}
for \(p \left (x \right )\). This is because we had to divide by this in the above step. This gives the following
singular solution(s), which also have to satisfy the given ODE.
\begin{align*} p \left (x \right ) = 1 \end{align*}
Solving for \(p \left (x \right )\) gives
\begin{align*}
p \left (x \right ) &= 1 \\
p \left (x \right ) &= \operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )+1 \\
\end{align*}
Substituing the above solution for \(p\) in (2A) gives
\begin{align*} u \left (x \right ) = x -1\\ u \left (x \right ) = -\operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )^{2}-2 \operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )+x -1\\ \end{align*}
In summary, these are the solution found for \(u(x)\)
\begin{align*}
u \left (x \right ) &= x -1 \\
u \left (x \right ) &= -\operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )^{2}-2 \operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )+x -1 \\
\end{align*}
For solution \(u \left (x \right ) = x -1\), since \(u=y^{\prime }\) then we now have a new
first order ode to solve which is
\begin{align*} y^{\prime } = x -1 \end{align*}
Since the ode has the form \(y^{\prime }=f(x)\), then we only need to integrate \(f(x)\).
\begin{align*} \int {dy} &= \int {x -1\, dx}\\ y &= \frac {1}{2} x^{2}-x + c_2 \end{align*}
For solution \(u \left (x \right ) = -\operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )^{2}-2 \operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )+x -1\), since \(u=y^{\prime }\) then we now have a new first order ode to solve which is
\begin{align*} y^{\prime } = -\operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )^{2}-2 \operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )+x -1 \end{align*}
Since the ode has the form \(y^{\prime }=f(x)\), then we only need to integrate \(f(x)\).
\begin{align*} \int {dy} &= \int {-\operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )^{2}-2 \operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )+x -1\, dx}\\ y &= \frac {2 \operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )^{3}}{3}+3 \operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )^{2}+4 \operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )+\frac {x^{2}}{2}-x + c_3 \end{align*}
In summary, these are the solution found for \((y)\)
\begin{align*}
y &= \frac {1}{2} x^{2}-x +c_2 \\
y &= \frac {2 \operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )^{3}}{3}+3 \operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )^{2}+4 \operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )+\frac {x^{2}}{2}-x +c_3 \\
\end{align*}
Will add steps showing solving for IC
soon.
Summary of solutions found
\begin{align*}
y &= \frac {1}{2} x^{2}-x +c_2 \\
y &= \frac {2 \operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )^{3}}{3}+3 \operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )^{2}+4 \operatorname {LambertW}\left ({\mathrm e}^{-1-\frac {x}{2}-\frac {c_1}{2}}\right )+\frac {x^{2}}{2}-x +c_3 \\
\end{align*}
Maple step by step solution
Maple trace
`Methods for second order ODEs:
Successful isolation of d^2y/dx^2: 2 solutions were found. Trying to solve each resulting ODE.
*** Sublevel 2 ***
Methods for second order ODEs:
--- Trying classification methods ---
trying 2nd order Liouville
trying 2nd order WeierstrassP
trying 2nd order JacobiSN
differential order: 2; trying a linearization to 3rd order
trying 2nd order ODE linearizable_by_differentiation
trying 2nd order, 2 integrating factors of the form mu(x,y)
trying differential order: 2; missing variables
`, `-> Computing symmetries using: way = 3
-> Calling odsolve with the ODE`, diff(_b(_a), _a) = (-_b(_a)+_a)^(1/2), _b(_a), HINT = [[1, 1]]` *** Sublevel 3 ***
symmetry methods on request
`, `1st order, trying reduction of order with given symmetries:`[1, 1]
Maple dsolve solution
Solving time : 0.063
(sec)
Leaf size : 122
dsolve(diff(diff(y(x),x),x)^2+diff(y(x),x) = x,y(x),singsol=all)
\begin{align*}
y &= \int \left (-{\mathrm e}^{2 \operatorname {RootOf}\left (\textit {\_Z} -x -2 \,{\mathrm e}^{\textit {\_Z}}+2+c_{1} -\ln \left ({\mathrm e}^{\textit {\_Z}} \left ({\mathrm e}^{\textit {\_Z}}-2\right )^{2}\right )\right )}+2 \,{\mathrm e}^{\operatorname {RootOf}\left (\textit {\_Z} -x -2 \,{\mathrm e}^{\textit {\_Z}}+2+c_{1} -\ln \left ({\mathrm e}^{\textit {\_Z}} \left ({\mathrm e}^{\textit {\_Z}}-2\right )^{2}\right )\right )}+x \right )d x -x +c_{2} \\
y &= \frac {2 \operatorname {LambertW}\left (-c_{1} {\mathrm e}^{-\frac {x}{2}-1}\right )^{3}}{3}+3 \operatorname {LambertW}\left (-c_{1} {\mathrm e}^{-\frac {x}{2}-1}\right )^{2}+4 \operatorname {LambertW}\left (-c_{1} {\mathrm e}^{-\frac {x}{2}-1}\right )+\frac {x^{2}}{2}-x +c_{2} \\
\end{align*}
Mathematica DSolve solution
Solving time : 17.332
(sec)
Leaf size : 172
DSolve[{(D[y[x],{x,2}])^2+D[y[x],x]==x,{}},y[x],x,IncludeSingularSolutions->True]
\begin{align*}
y(x)\to \frac {2}{3} W\left (e^{-\frac {x}{2}-1-\frac {c_1}{2}}\right ){}^3+3 W\left (e^{-\frac {x}{2}-1-\frac {c_1}{2}}\right ){}^2+4 W\left (e^{-\frac {x}{2}-1-\frac {c_1}{2}}\right )+\frac {x^2}{2}-x+c_2 \\
y(x)\to \frac {2}{3} W\left (-e^{\frac {1}{2} (-x-2+c_1)}\right ){}^3+3 W\left (-e^{\frac {1}{2} (-x-2+c_1)}\right ){}^2+4 W\left (-e^{\frac {1}{2} (-x-2+c_1)}\right )+\frac {x^2}{2}-x+c_2 \\
y(x)\to \frac {x^2}{2}-x+c_2 \\
\end{align*}